A randomised, multi-centre trial of total ankle replacement versus ankle arthrodesis in the treatment of patients with end stage ankle osteoarthritis (TARVA): statistical analysis plan - Muller, Patrick (Trials, 2020)
BACKGROUND: The total ankle replacement versus ankle arthrodesis (TARVA) trial aims to determine which surgical procedure confers the greatest improvement in pain-free function for patients with end-stage ankle osteoarthritis. Both procedures are effective but there has not yet been a direct comparison to establish which is superior. This article describes the statistical analysis plan for this trial as an update to the published protocol. It is written prior to the end of patient follow-up, while the outcome of the trial is still unknown. DESIGN AND METHODS: TARVA is a randomised, un-blinded, parallel group trial of total ankle replacement versus ankle arthrodesis. The primary outcome is the Manchester-Oxford Foot Questionnaire walking/standing domain score at 52 weeks post-surgery. Secondary outcomes include measures of pain, social interaction, physical function, quality of life, and range of motion. We describe in detail the statistical aspects of TARVA: the outcome measures, the sample size calculation, general analysis principles including treatment of missing data, the planned descriptive statistics and statistical models, and planned subgroup and sensitivity analyses. DISCUSSION: The TARVA statistical analysis will provide comprehensive and precise information on the relative effectiveness of the two treatments. The plan will be implemented in January 2020 when follow-up for the trial is completed. TRIAL REGISTRATION: ISRCTN registry number 60672307, ClinicalTrials.gov registration number NCT02128555. Registered 1 May 2014. Recruitment started in January 2015 and ended in January 2019.